Renal haemodynamic, microcirculatory, metabolic and histopathological responses to peritonitis-induced septic shock in pigs - Chvojka, Jiri; Sykora, Roman; Krouzecky, Ales; Radej, Jaroslav; Varnerova, Veronika; Karvunidis, Thomas; Hes, Ondrej; Novak, Ivan; Radermacher, Peter; Matejovic, Martin (Critical care (London, England), 2008)
INTRODUCTION: Our understanding of septic acute kidney injury (AKI) remains incomplete. A fundamental step is the use of animal models designed to meet the criteria of human sepsis. Therefore, we dynamically assessed renal haemodynamic, microvascular and metabolic responses to, and ultrastructural sequelae of, sepsis in a porcine model of faecal peritonitis-induced progressive hyperdynamic sepsis. METHODS: In eight anaesthetised and mechanically ventilated pigs, faecal peritonitis was induced by inoculating autologous faeces. Six sham-operated animals served as time-matched controls. Noradrenaline was administered to maintain mean arterial pressure (MAP) greater than or equal to 65 mmHg. Before and at 12, 18 and 22 hours of peritonitis systemic haemodynamics, total renal (ultrasound Doppler) and cortex microvascular (laser Doppler) blood flow, oxygen transport and renal venous pressure, acid base balance and lactate/pyruvate ratios were measured. Postmortem histological analysis of kidney tissue was performed. RESULTS: All septic pigs developed hyperdynamic shock with AKI as evidenced by a 30% increase in plasma creatinine levels. Kidney blood flow remained well-preserved and renal vascular resistance did not change either. Renal perfusion pressure significantly decreased in the AKI group as a result of gradually increased renal venous pressure. In parallel with a significant decrease in renal cortex microvascular perfusion, progressive renal venous acidosis and an increase in lactate/pyruvate ratio developed, while renal oxygen consumption remained unchanged. Renal histology revealed only subtle changes without signs of acute tubular necrosis. CONCLUSION: The results of this experimental study argue against the concept of renal vasoconstriction and tubular necrosis as physiological and morphological substrates of early septic AKI. Renal venous congestion might be a hidden and clinically unrecognised contributor to the development of kidney dysfunction.
Keywords: Animals; Kidney; mikrocirkulace; Research Design; peritonitida; ultrasonografie; Peritonitis; Hemodynamics; hemodynamika; Laser-Doppler Flowmetry; prasata; Ultrasonography; Shock, Septic; septický šok; Czech Republic; Swine; Microcirculation; laser doppler flowmetrie; Česká republika; zvířata; ledviny; výzkumný projekt